Share resources through the largest interlibrary loan network. Issue 4 (21st November 2016) - Burke, Gemma; Duncan, Erin; Smither, JL
Abstract : Purpose: The paper aims to show how using a resource-sharing service can help you provide more resources to your users. Design/methodology/approach: This paper discusses interlibrary loan challenges and opportunities, specifically with reference to WorldShare Interlibrary Loan. Findings: This paper describes the service that connects libraries to the largest cooperative resource-sharing network with more than 10, 000 borrowing and lending libraries worldwide, the possibilities for the future, facts and figures and how libraries around the world have used the solution successfully. Originality/value: This paper looks at how WorldShare Interlibrary Loan can help libraries overcome the challenges that they face regarding resource sharing.